Successful Presentations: Step-by-Step Strategies to Get Results Fast - Brian Lomas (Get brilliant results fast, 2012)
Presenting is a core business skill. Whether your aim is to inspire a large group, to impart knowledge, or to make things happen quickly, effective presentation skills are a must-have. We explain how to speak confidently to an audience of any size, with impact, clarity and flair.Presenting is not easy, whatever level you are at. The author, an expert presenter himself, describes how to deal with tricky questions and unforeseen problems, how to research and plan your presentation, and most importantly, how to engage your audience.This book will help you:â€" Manage your nerves to deliver a powerful presentionâ€" Develop your own, successful styleâ€" Leave your audience wanting moreâ€" Handle tricky situationsâ€" Learn when and how to use PowerPoint